An experimental study on the compressive response of CFRP honeycombs with various cell configurations. (1st April 2019) - Pehlivan, Levent; Baykasoğlu, Cengiz
Abstract: The experimental investigation on the compressive response of carbon fiber reinforced polymer (CFRP) honeycombs with various cell configurations was carried out in the present work. The CFRP honeycomb specimens were manufactured by corrugation technique, in which the prepreg CFRP sheets were first corrugated into the certain shape using corrugated aluminum moulds under heat and pressure, and then the corrugated CFRP sheets were glued and stacked to construct honeycomb specimens. Twenty-seven groups of specimens were experimentally tested to examine the effects of cell geometry (i.e., square, circular, and hexagonal), cell wall thickness and height on the quasi-static out-of-plane crushing performance of the honeycombs. The square, circular, and hexagonal honeycomb specimen groups were designed to have almost the same weights. The results showed that the cell wall thickness is an significant parameters on the overal crushing response of the CFRP honeycombs while the out-of-plane compressive strenght of the honeycombs is generally independent of the height. It is observed that the hexagonal specimen groups have generally superior crushing performance in comparison with the square and circular counterparts due to their large double foil bonding surfaces. The experimental results also revealed that the crushing properties of the honeycomb structures with the core densities of 157–282 kg/m 3 could be increased more than two times with the appropriate selection of cell configurations. Highlights: CFRP honeycombs with various cell configurations are manufactured by corrugation technique. The cell geometry, cell wall thickness and heights are considered as design parameters. The quasi-static compressive response of CFRP honeycombs are investigated. The response of honeycombs could be significantly enhanced at almost the equal mass basis. The test results are also added in the Ashby material strength versus density map.